Kinetics of the thermal degradation of poly(lactic acid) obtained by reactive extrusion: Influence of the addition of montmorillonite nanoparticles. (December 2015) - Carrasco, F.; Santana, O.; Cailloux, J.; Maspoch, M.Ll.
Abstract: A reactive extrusion-calendering process was used in order to manufacture sheets with a nominal thickness of 1 mm of poly(lactic acid) and its nanocomposite with 2.5% of an organo-modified montmorillonite. During processing, the properties of the melt were stabilized and enhanced by the addition of 0.5% of a styrene-acrylic multi-functional-epoxide oligomeric reactive agent. The general analytical equation has been used in order to evaluate the kinetic parameters of the thermal degradation of poly(lactic acid) obtained by reactive extrusion and its nanocomposite. Various empirical and theoretical solid-state mechanisms have been tested to elucidate the best kinetic model. In order to reach this goal, master plots have been constructed by means of standardized conversion functions. Given that it is not always easy to visualize the best accordance between experimental and theoretical values of standardized conversion functions, a new index has been developed to quantitatively discern the best mechanism. By doing that, it has been possible to determine the right activation energy of the thermal degradation. It has been demonstrated that the best theoretical mechanism was the random scission of macromolecular chains within the polymer matrix. This was also in accordance with an empirical kinetic model based on an autocatalytic kinetic model. The presence of montmorillonite nanoparticles has been beneficial and has enhanced the thermal stability of poly(lactic acid).